Profitability Of Some Bari Released Crop Varieties In Some Locations Of Bangladesh (Bangladesh Journal of Agricultural Research, 2011)
An attempt was made to asses the costs and returns from the cultivation of selected crops in different locations. Fifty farmers were selected for collecting data for each crop through random sampling for the year 2006-07. Study revealed that per hectare total costs were Tk. 51341, Tk. 32275, Tk. 20983, Tk. 27819, Tk. 63012, Tk. 61928, Tk. 87828, Tk. 65163, and Tk. 57775 for the cultivation of maize, groundnut, mungbean, sweet potato, cabbage, cauliflower, tomato, cucumber, and okra, respectively. Sample farmers received Tk. 31280, Tk. 23221, Tk. 12957, Tk. 70981, Tk. 56546, Tk. 72820, Tk. 247076, Tk. 61437 and Tk. 94822 per hectare as net returns from the cultivation of maize, groundnut, mungbean, sweet potato, cabbage, cauliflower, tomato, cucumber, and okra, respectively. The benefit cost ratios over total costs were 1.61, 1.72, 1.62, 3.55, 1.90, 2.17, 3.72, 1.94, and 2.64 for the cultivation of maize, groundnut, mungbean, sweet potato, cabbage, cauliflower, tomato, cucumber, and okra, respectively. High costs of fertilizers and insecticides were the major constraints to higher production for most of the crops as mentioned by the sample farmers.   Keywords: Profitability; crops; locations. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9235 BJAR 2011; 36(1): 111-122